The Dual-Coding Theory and Digital Media: The Effect of Nursery Rhymes on Teaching Vocabulary - Tiara Damayanti; Yohanes Gatot Sutapa Yuliana; Sudarsono Sudarsono (Lectura : Jurnal Pendidikan, 2023)
Most of the vocabulary in English has differences in written and spoken form, then it also takes time for the learners to recognize and memorize the new vocabularies that they have learned before they implement it in their conversation. The dual-coding theory believes when verbal and non-verbal stimuli are connected, it brings a deeper understanding and better imaging of certain things. The objectives of this study are to find out whether the use of nursery rhymes is significantly effective or not, and how effective the use of nursery rhymes is for vocabulary teaching processes based on the perspective of the dual-coding theory and the aspect of vocabulary knowledge to the elementary students. The participants of this study are 64 of the Year-3 students at MI Ushuluddin Singkawang in 2022/2023 of academic year divided into two groups, control and experimental group. The data were taken from the students’ pretest and posttest results and tools to measure the data were thirty numbers of short answer questions. The findings show nursery rhymes are significantly effective for the vocabulary teaching processes to the elementary students. Nursery rhymes not only run mechanically but also activate the students’ experiences, emotions, and thoughts through the process of repeating, reciting, then practicing related to the aspect of form, meaning, and use in vocabulary knowledge. All of these processes in the classroom bring a better recall for them specifically related to vocabulary learning.